Bidirectional wireless power transfer: Bridging electric vehicles and the grid through converter analysis, coil topologies, and communication protocol review - M. Venkatesan; Narayanamoorthi R; Petr Kacor; Matous Vrzala (Results in Engineering)
The Electric Vehicle (EV) emerges as a promising alternative for curbing greenhouse gas emissions compared to traditional Internal Combustion Engine (ICE) vehicles. Recent strides in power converter technology enable the bidirectional flow of electrical energy between EVs and the Grid (V2 G) seamlessly. However, conventional plug-in charging methods necessitate human intervention for EV participation in V2 G operations. Consequently, wireless power transfer (WPT) technology emerges as a viable solution, eliminating the need for manual intervention in enabling bidirectional operation for EVs. Furthermore, the integration of distributed local networks of energy storage units into the grid becomes feasible through the WPT approach, utilizing energy from stationary EV batteries. Ongoing advancements in converter technology, coil design, and controller modeling play a pivotal role in the efficient development of bidirectional WPT technologies. This paper delves into a comprehensive analysis of various bidirectional DC/DC converter configurations, focusing on active power transformation between V2 G and G2V. Additionally, it explores diverse types, structures, and shapes of wireless power-transferring coils that are well-suited for bidirectional WPT applications. The discussion extends to encompass various communication standards and modes employed in wireless communications for V2 G operations. The overview encompasses EV communications, procedural standards, computational methods, and ongoing research on various types of wireless charging systems.